Multidisciplinary approaches: esthetic restorations after orthodontic treatment. - (:unkn) unknown (My University, 1997)
After orthodontic treatment prosthetic restorations are sometimes still necessary to improve the patient esthetics. After routine orthodontic procedures (alignment of teeth and achievement of functional occlusion) conventional crowns and bridges are used. In this case study, the follow-up results of four patients are presented. They had been treated by various disciplines; orthodontics, plastic surgery and prosthodontics. Satisfactory esthetics and function were achieved with all patients.